Child restraint system: lessons learned from global best practices - Monjurul Hoque, Mohammod Arif Uddin; K. C. Mani, Kulanthayan; Ahmed Khan, Tanveer (Human Resource Management Academic Research Society, 2021)
Road traffic injury is one of the major but neglected public health challenges globally. According to WHO (2018), road crash kills about 1.35 million people while it maims another 50 million, each year globally. Rapid urbanization and industrialization throughout the world have accelerated the growth of transport systems for faster communication. As a result, motor vehicles' mobility has increased to a great extent making roads more vulnerable for road users. Commuters’ safety has, therefore, emerged as an issue of critical concern. Automobile manufacturers have taken passenger safety with due importance and have been improvising vehicles’ safety measures. The major objective of this paper is to do a literature review of the global best practices. This paper investigates the effectiveness of the current vehicle safety system in ensuring child passengers' safety in a vehicle. Due to the unique physique, traveling children require safety devices that consider their age, height, and weight. An efficient way to improve that safety in moving vehicles is to use Child Restraint Systems (CRS) to ‘hold’ them during a probable collision. Unfortunately, there is little evidence in low-and middle-income countries (LMICs) relative to high-income countries (HICs). Increasing research on this aspect is vital, especially for LMICs, to make the device more straightforward and effective. This literature review deals with the existing practices regarding child safety in road journeys and probable steps for remedies and improvement, which could eventually be used as a guideline for transferring lessons learned from HICs to LMICs.